Recreational Water Illnesses - Erica Leoni (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The safety of recreational waters is affected by numerous variables such as the microbiological and chemical quality of water, the number and health conditions of the users, and the correct functioning of all technological installations used for water treatment. By evaluating the various health risks related to exposure to swimming pools, spas, and surface waters, this Special Issue seeks to address the proper management of waters used for recreational purposes, both in natural and built environments. This Issue contains 12 scientific papers. The first four, three of which are literature reviews, illustrate the epidemiological picture of infections related to recreational waters, by describing cases and outbreaks caused by both traditional and emerging microorganisms. The following four papers concern the microbiological monitoring of swimming pools, gardens, estuarine areas, and therapeutic spas. Two of these also analyse the distribution of antibiotic-resistant bacteria and the associated transmission risks. The relationship between microbial indicators and pathogens in recreational water is analysed by the following two papers, one of which is an experimental study on the survival of Salmonella and Escherichia coli in estuarine bank sediments and the other of which is an exhaustive literature review. The last two papers are focused on the development of risk control approaches, including the validation of questionnaire methods to quantify recreational water ingestion and the application of traditional and innovative technologies in water treatment.